Informacy - Neelameghan, A. (DESIDOC Journal of Library & Information Technology, 2002)
In this articie the author discusses the present IT and te!ecommunication scenario in India and the opportunity offered by the international market. To tap this expanding market, he conceptualises user education exercises and lnforrnacy programme at various levels leading to developing information oriented culture in the society. http://dx.doi.org/10.14429/dbit.15.6.3205